Teachers' Strategies in Teaching Speaking Skills at MTSN 8 Agam - Siti Nurhalija; Syahrul Syahrul; Yurni Yurni (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study was to determine the teacher's strategy in teaching speaking. The problem in this study is that students feel unconfident in speaking English and also have a limited vocabulary. This type of research is called qualitative research. The sample for this study is the MTSN 8 Agam teacher. The instruments used in this study were observations and interviews. The results of this study, the strategies used by teachers in teaching speaking are drill, roleplay, simulation, and group discussion.